Automatic Taxiing Direction Control System for Carrier-Based Aircraft - Krawczyk, Mariusz; Szczepański, Cezary; Zajdel, Albert (Transactions on Maritime Science, 2019)
This paper solves the problem of automatic taxiing direction control of carrier-based aircraft. On modern aircraft carriers, taxiing aircraft either propel themselves using their own engines or are towed by specialised tugs, which requires dedicated personnel and assets. The automatization of this process would simultaneously increase aircraft flow and decrease the number of personnel and assets required. The key challenge in the automatization of this type of process is the development of an automatic control system capable of performing the requisite tasks, which our researchers managed to do. First, the specific conditions of taxiing on-board carriers were analysed and modelled. The model of a fixed-wing aircraft best suited to this purpose was identified and the proper method of automatic control – ADRC – chosen. The algorithm used in the method to facilitate effective direction control of a taxiing aircraft was formulated and extensively tested. The results of automatic taxiing simulation for F/A-18 aircraft have been presented. The conclusion is that the ADRC type control algorithm can ensure effective automatic control of taxiing aircraft.